Competition of politicians for incentive contracts and elections - Gersbach, Hans (CESifo working papers, 2001)
When politicians have lower discount factors than voters, democratic elections cannot sufficiently motivate politicians to undertake long-term socially beneficial projects. When politicians can offer incentive contracts which become effective upon reelection, the hierarchy of contracts and elections can alleviate such inefficient decision-making in politics. This mechanism still works if the public cannot commit itself to a reelection scheme or if the public is unsure about the politicians time preferences. In the non-commitment case, incentive contracts may need to include a golden parachute clause.Keywords: Incentive contracts, politicians, long-term policies, elections and contracts, golden parachute clause.
Keywords: Arbeitspapier; Graue Literatur; Spieltheorie; Politische Entscheidung; Wahlverhalten; Asymmetrische Information; Ökonomische Theorie der Demokratie